Neurociencias y derecho penal desde una perspectiva funcional de la mente (2015)
On the matter of the discussion about the reach of the conclusions to which some neuroscientists have arrived after conducting relatively recent experiments regarding subjects that, like the possibility of individual freedom, are crucial to the legitimacy